When intentions meet reality: Consonance and dissonance in teacher approaches to peer assessment - Sandvoll, Ragnhild Sofie (Canadian Journal of Higher Education, 2014)
This article focuses on teachers’ experiences in implementing peer assessment with first semester students. It explores the relationship between teachers’ conceptions of teaching and their approach to peer assessment, where both conceptions and approaches are described as being either learning focused or content focused. Drawing upon analysis of interviews with eight teachers, the study found that one had a consonant view of the interrelationship between conceptions of teaching and approaches to peer assessment, while the remaining seven described their conceptions of teaching and their approaches to peer assessment with a combination of learning-focused and content-focused statements. These statements are labelled as dissonant. Discussion focuses on implications of consonant and dissonant relationships between conceptions of teaching and approaches to peer assessment for implementation of peer assessment; it also addresses academic development issues. The study reveals that when implementing new methods (here, peer assessment), underlying assumptions will impact on the nature of teacher engagement.